INFLUENCE OF THERMAL BARRIER TYPE CERAMIC LAYER’S CHEMICAL COMPOSITION AND QUICK THERMAL SCHOCK ON THEIR POROSITY AND ADHERENCE - Florin Ciofu (Fiabilitate şi Durabilitate)
The paper presents several types of thermal barrier type ceramic layers and the variations concerningtheir porosity and adherence related with their chemical composition. The structural and compositionalcharacterization of the obtained layers was performed by electron microscopy, one of the most relevantinvestigation methods in order to choose the optimum composition for the external layer deposited on copperdevices. The effect of quick thermal shock on the samples porosity and on chemical elements distribution alongthe layer’s thickness was also taken into account.